Optimasi flotasi bijih nikel laterit menggunakan depresan pati singkong karet (Manihot glaziovii) dengan variasi konsentrasi pati dan pH terhadap recovery nikel - Rantang, Cornelia Kesia; Almi Lestari, Mirna; Yoretno Y, Putri; Caludia Rony, Putri; Imanuel Tikupadang, Ruberto; Sira Sarungallo, Rosalia (Cassowary, 2025)
ABSTRACT: This research aims to characterize the chemical composition of laterite nickel ore and analyze the effect of variations in the mass of cassava rubber starch depressant (Manihot glaziovii) and the pH of the flotation solution on nickel recovery and the content of gangue minerals (Fe2O3 and SiO2) in the flotation process. The laterite nickel ore used was obtained from Southeast Sulawesi. The research was conducted experimentally in the laboratory with pH variations of 5, 7, and 9 and starch depressant masses of 0, 0.1, 0.3, and 0.5 g. The collector used was sodium oleate, and pine oil was used as a frother. The results showed that the laterite nickel ore used as raw material has typical characteristics of laterite ore with a low Ni content and high gangue content. Variations in the mass of cassava rubber starch depressant and pH affected nickel recovery and the selectivity of separation toward gangue minerals. Under acidic conditions (pH 5), increasing the starch mass up to 0.3 g decreased nickel recovery from 58.26% to 36.75%. At neutral pH (pH 7), a recovery of 69.62% was obtained, while at basic pH (pH 9) and a starch mass of 0.5 g, the highest nickel recovery of 76.61% was achieved. However, the use of cassava rubber starch has not yet shown optimal selectivity in reducing Fe2O3 and SiO2 contents. Research using cassava rubber starch has potential as a natural, economical, and environmentally friendly depressant to improve nickel recovery in the flotation process of laterite nickel ore, although further optimization is still needed to improve selectivity toward gangue minerals.